ChemInform Abstract: Synthetic Methods for Compounds Having CF3‐S Units on Carbon by Trifluoromethylation, Trifluoromethylthiolation, Triflylation, and Related Reactions. Issue 15 (April 2015) - Xu, Xiu‐Hua; Matsuzaki, Kohei; Shibata, Norio
Abstract: Review: 468 refs.